1996
DOI: 10.1006/ffta.1996.0015
|View full text |Cite
|
Sign up to set email alerts
|

Improved Bounds in the Multiple-Recursive Matrix Method for Pseudorandom Number and Vector Generation

Abstract: DEDICATED TO PROFESSOR E. HLAWKA ON THE OCCASION OF HIS 80TH BIRTHDAYThe multiple-recursive matrix method is a general linear method for the generation of uniform pseudorandom numbers and vectors which was introduced and studied in earlier papers of the author. In this paper we improve on various bounds in this method by using information on -splitting subspaces of finite fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 7 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…After a preliminary version of this paper was prepared, we found that the seemingly new notion of a σ-LFSR can, in fact, be traced back to the work of Niederreiter (1993Niederreiter ( -1996 mainly in the context of pseudorandom number generation. Indeed, in a series of papers [12,13,14,15], Niederreiter has introduced the so called multiple recursive matrix method and the notion of recursive vector sequences. The latter are essentially the same as sequences generated by a σ-LFSR, modulo a natural isomorphism between the field F q m with q m elements and the vector space F m q of dimension m over The question of counting the number of primitive σ-LFSRs of a given order n over F q m is considered in [13, p. 11] under a different guise (cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After a preliminary version of this paper was prepared, we found that the seemingly new notion of a σ-LFSR can, in fact, be traced back to the work of Niederreiter (1993Niederreiter ( -1996 mainly in the context of pseudorandom number generation. Indeed, in a series of papers [12,13,14,15], Niederreiter has introduced the so called multiple recursive matrix method and the notion of recursive vector sequences. The latter are essentially the same as sequences generated by a σ-LFSR, modulo a natural isomorphism between the field F q m with q m elements and the vector space F m q of dimension m over The question of counting the number of primitive σ-LFSRs of a given order n over F q m is considered in [13, p. 11] under a different guise (cf.…”
Section: Introductionmentioning
confidence: 99%
“…After a preliminary version of this paper was prepared, we found that the seemingly new notion of a σ-LFSR can, in fact, be traced back to the work of Niederreiter (1993Niederreiter ( -1996 mainly in the context of pseudorandom number generation. Indeed, in a series of papers [12,13,14,15], Niederreiter has introduced the so called multiple recursive matrix method and the notion of recursive vector sequences.…”
Section: Introductionmentioning
confidence: 99%